The Wahdatul Ulum Paradigm: Its Idea and Basis, and Consequences for SD/MI Level Teachers - Nurhaliza, Siti; Manalu, Sri Rahmayani; Sukandi, Sukandi; Salminawati, Salminawati (Jurnal Basicedu, 2023)
According to the Islamic educational paradigm known as Wahdatul Ulum, knowledge comes from the One Supreme Being (Allah swt.). Many academic institutions are now concerned with using this paradigm-based teaching to instill the significance of religious education in future teachers, especially those who will teach at the SD/MI level. The purpose of this study is to explain the ideas and principles behind the wahdatul ulum paradigm and the consequences they have for MI/SD teachers. This kind of research combines the qualitative research approach with the literature study method. gathering information and materials for study analysis employing scientific literature, such as articles, books, proceedings, and the final project (thesis, thesis or dissertation). Additionally, research materials were double-checked to ensure the data's veracity, and reliable websites like Google Scholar and Sinta were identified. The study's findings show that (1) the wahdatul ulum paradigm emphasizes the connections between the holistic system of the universe to knowledge, leading to the belief that acquired knowledge and perennial knowledge are integral (one unit or whole); (2) the Koran, hadith, and the universe serve as the paradigm's foundation; (3) using this paradigm for SD/MI teachers has the implications of strengthening their religious and integral personalities.